2013
DOI: 10.1007/s00125-013-3006-x
|View full text |Cite
|
Sign up to set email alerts
|

Nupr1 deletion protects against glucose intolerance by increasing beta cell mass

Abstract: Aims/hypothesis The stress-activated nuclear protein transcription regulator 1 (NUPR1) is induced in response to glucose and TNF-α, both of which are elevated in type 2 diabetes, and Nupr1 has been implicated in cell proliferation and apoptosis cascades. We used Nupr1 −/− mice to study the role of Nupr1 in glucose homeostasis under normal conditions and following maintenance on a high-fat diet (HFD). Methods Glucose homeostasis in vivo was determined by measuring glucose tolerance, insulin sensitivity and insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…Other transgenic mice have established the link between inflammation and aberrant glucose metabolism [136][137][138]. Likewise, several genes important for normal beta cell function and maintaining beta cell mass have been detected using knock-out mice [139][140][141][142]. Often knock-out mice are subjected to a high fat diet to ascertain whether the gene of interest can compensate for an insulin-resistant state [143,144].…”
Section: Genetic Manipulation: Methods To Understand Insulin Resistanmentioning
confidence: 99%
“…Other transgenic mice have established the link between inflammation and aberrant glucose metabolism [136][137][138]. Likewise, several genes important for normal beta cell function and maintaining beta cell mass have been detected using knock-out mice [139][140][141][142]. Often knock-out mice are subjected to a high fat diet to ascertain whether the gene of interest can compensate for an insulin-resistant state [143,144].…”
Section: Genetic Manipulation: Methods To Understand Insulin Resistanmentioning
confidence: 99%
“…Messenger RNAs were extracted from pancreas, islets, MIN6 beta cells, perigonadal fat and liver, purified and concentrated using Invitrogen RNeasy minikits before being reverse-transcribed into cDNAs [18]. Quantitative PCR amplifications of Nupr1, Hsp1a and β-actin were performed using the following conditions: denaturation at 95°C for 10 min, DNA amplification using 35-40 cycles at 95°C for 1 s, 60°C for 10 s and 72°C for 15 s. The primers used were: Nupr1 (F) 5′-gaagctgctgccaataccaacc-3′ and (R) 5′-tagctctgcccgtctaccctc-3′; Hspa1a (F) 5′-gcactgccccgctgatgtga-3′ and (R) 5′-gtggcccaggggagagtcca-3′; β-actin (F) 5′-atgaagtgtgacgttgacatccgt-3′ and (R) 5′-cctagaagcatttgcggtgcacgatg-3′.…”
Section: Gene Expression Analysesmentioning
confidence: 99%
“…However, Nupr1 knockout mice fed a normal diet were insulin resistant, so complete ablation of Nupr1 is not an ideal scenario for appropriate control of glucose homeostasis. Our microarray analysis indicated that Nupr1 regulated expression of Hspa1a, which codes for Hsp70 expression [18], so we hypothesised that partial loss of Nupr1 could circumvent the potentially deleterious effects seen with complete Nupr1 knockout on a normal diet, while conferring beneficial effects through increased expression of Hsp70 and consequent improved insulin sensitivity. In the current study we therefore characterised the metabolic phenotype of Nupr1 haplodeficient C57BL/6 mice under normal conditions and when fed a high fat diet to induce insulin resistance and glucose intolerance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…During GTTs, in addition to blood glucose measurements, further 50 ml blood samples were taken by capillary from a superficial incision on the tail vein at both baseline and 30 min after glucose administration for the separation of plasma and measurement of insulin levels. Other studies have previously taken additional plasma samples during mouse GTTs for the measurement of plasma insulin (Ahren et al 2008, Andrikopoulos et al 2008, Barbosa-Sampaio et al 2013, and modern insulin assays allow the measurement of insulin levels in plasma samples as small as 5 ml. However, for the purposes of this study, the critical information required was the baseline fasting plasma insulin level and the peak insulin secretion in response to the glucose challenge (30 min).…”
Section: Scenario 1 -Assessing Glucose Homeostasis In Pregnant Micementioning
confidence: 99%